Poverty Alleviation Strategy by Baitul Mall Hidayatullah : (Case Study at Laznas BMH Makassar City) - Rostinawati Manaf; Muslimin Kara; Nasrullah Bin Sapa (LP2M IAIN Palopo, 2026)
Poverty remains a complex and multidimensional fundamental problem, impacting not only the economic aspects but also social, educational, and public health. This condition encourages the role of Islamic philanthropic institutions such as Baitul Maal Hidayatullah (BMH) Makassar to participate in poverty alleviation efforts. The main problem is then broken down into several sub-problems or research questions, namely: 1) What is the form of implementation of the Baitul Maal Hidayatullah (BMH) program?, 2) How is the application of the CIBEST approach and decile analysis in measuring the level of welfare of mustahik at Baitul Maal Hidayatullah (BMH) Makassar?, 3) What strategies can be formulated based on the SWOT analysis to increase the effectiveness of the BMH (Baitul Mall Hidayatullah) program in supporting the improvement of the welfare of poor people in Tamalanrea District? The research method used in this study is a qualitative approach with a case study research type.This study uses sampling through purposive sampling techniques.was conducted at BMH Makassar City, with data collection through in-depth interviews with managers, beneficiaries, and related stakeholders, field observations, and document analysis. Data analysis techniques used included SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to identify internal and external factors of the institution, as well as the CIBEST approach and decile analysis to measure the level of welfare of mustahik before receiving assistance. The results of the study indicate that the implementation of BMH Makassar programs, both consumptive and productive, namely education, da'wah and productive economic programs. The CIBEST approach and decile analysis prove that most mustahik are still in the lower welfare layer, thus requiring more targeted and sustainable interventions. The SWOT analysis revealed that BMH has strengths in transparent governance, technology utilization, and institutional legitimacy, but still faces weaknesses in program sustainability and synergy with other institutions, as well as threats from low zakat awareness and overlapping beneficiaries. The poverty alleviation strategy of BMH Makassar includes optimizing the management of ZISWAF (Islamic charity) based on sharia principles, strengthening synergies with government and private institutions, and developing sustainable empowerment programs, such as skills training, providing business capital, and mentoring. BMH also integrates technology in fundraising and aid distribution, and strengthens partnership networks to expand the program's reach and effectiveness. This strategy is expected to increase the independence of those entitled to receive alms, strengthen the social safety net, and encourage the realization of a more prosperous and equitable society.